Identification of core ion cyclotron instabilities on HL-2A tokamak - Linzi Liu; Ruihai Tong; Xiaolan Zou; Haotian Chen; Yang Chen; Guanqi Dong; Guangzhou Hao; Xiaoxue He; Yuxiao Han; Xiaoquan Ji; Anshu Liang; Bo Li; et al. (Nuclear Fusion, 2023)
Instabilities in multiplies of ion cyclotron frequency range are identified and termed as core ion cyclotron emission (ICE) in recent HL-2A neutral beam injection heated experiments. Characteristics of the core ICE are presented, including frequency dependence and harmonics features. The detected frequencies are found to agree well with the multiplies of the deuterium cyclotron frequency around the magnetic axis. Additionally, the core ICE exhibits a predominantly compressional property. Observations of distinct spectrum features and individual excitation of each harmonic have demonstrated that the core ICE harmonics are independent multiple modes. Notably, the variation of plasma current is a necessary condition for exciting the 4th harmonic ICE individually. The results suggest that the drive mechanism of core ICE varies between the different frequency ranges.